Abstract 18627: The Relative Contribution of Perfusion vs. Congestion in Predicting Adverse Outcomes in Heart Failure With Preserved Ejection Fraction - Jani, Vivek P; Vaishnav, Joban; Vungarala, Soumya; Hahn, Virginia S; Kass, David A; Sharma, Kavita (Circulation (New York, N.Y.), 2023)
Background: Heart Failure with Preserved Ejection Fraction (HFpEF) constitutes greater than half of all heart failure (HF) patients with limited therapies. There are limited data on the role of congestion versus perfusion in prognosticating outcomes. Methods: A total of 243 patients seen at the Johns Hopkins HFpEF Clinic between 2011-2023 with HFpEF and RHC were included for analysis. Subjects were stratified into congestion and perfusion groups based on the median PCWP and CI, which were 15 mmHg and 2.44 L/min/m2, respectively. Groups were assigned as follows: dry-warm (PCWP < 15 mmHg, CI ≥ 2.44 L/min/m2), wet-warm (PCWP ≥ 15 mmHg, CI ≥2.44 L/min/m2), dry-cold (PCWP < 15 mmHg, CI < 2.44 L/min/m2), and wet-cold (PCWP ≥ 15 mmHg, CI < 2.44 L/min/m2), seen in Figure 1A. Results: Subjects with hypoperfusion (wet-cold and dry-cold) were older (p=0.01), more likely to have atrial fibrillation (p<0.0001), had worse RV function (p=0.002), and had elevated NT-proBNP (p=0.0001) compared to subjects with normal perfusion. Congested patients were more likely female (p=0.002), had higher BMI (p=0.02), higher creatinine (p=0.005), evidence of metabolic syndrome, including elevated fasting glucose (p=0.0008), elevated cholesterol (p=0.01), and LVH on echocardiography (p=0.002). Kaplan-Meier survival analysis of the hemodynamic profiles for a combined end point of all-cause mortality and HF hospitalization revealed that congested profiles exhibited the lowest event free survival compared to the dry profiles (logrank p=0.008; Figure 1B) and of these, the wet-warm subjects had the lowest event-free survival at 36 months. Conclusion: Unlike in prior HF studies, congestion in HFpEF appears to be concomitant with obesity and metabolic syndrome. Moreover, while consistent with prior studies that congestion drives outcome differences compared to perfusion, wet-warm HFpEF patients appear to have the lowest event free survival as opposed to wet-cold patients as in other forms of HF.